ANALYSIS OF FACTORS AFFECTING EMPLOYEE LOYALTY AT THE GORONTALO HARBORMASTER AND PORT AUTHORITY OFFICE - Marno A Suleman; Rizal; Mohammad Ikbal Kadir (Journal of Economic, Business, and Administration (JEBA), 2026)
Employee loyalty plays a crucial role in ensuring organizational effectiveness, service quality, and long-term sustainability, particularly in public sector institutions. This study aims to identify the internal and external factors influencing employee loyalty at the Gorontalo Harbormaster and Port Authority Office (KSOP Gorontalo) and to explore how employees perceive and experience these factors within the organizational environment. A qualitative research approach with a phenomenological design was employed to gain an in-depth understanding of employees’ lived experiences related to loyalty. Informants were selected using purposive sampling based on their organizational roles, work experience, and knowledge of institutional practices. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal that job satisfaction is the primary internal factor affecting employee loyalty, particularly through effective communication, recognition, organizational support, and opportunities for career development. Government policies emerged as the most influential external factor, shaping work systems, technological adaptation, and service delivery processes. Furthermore, employees perceive loyalty as a multidimensional concept characterized by organizational pride, emotional attachment, commitment to public service, and a sense of belonging. The study concludes that employee loyalty is strengthened when organizational practices align with employees’ expectations and professional aspirations. These findings provide practical insights for improving human resource management and sustaining employee commitment within public sector organizations.